Optimization of Nutrition in Supporting Child Growth and Development - Afaf Ramadhani; Sri Dewi Wahyuni; Abelya Agusfiranda; Elza Elvania; Nadira Seftiani; Syahrul Khairati (Penerbit Hellow Pustaka, 2024)
Optimal nutrition is very important to support the growth and development of children, both from the aspect of health, and also their cognitive development. This study aims to explain the important components of nutrients such as micronutrients (vitamins and minerals) and macronutrients (carbohydrates, proteins, and fats), as well as how they impact children's physical and mental growth, as this research can specifically be a reference for making healthy foods and balanced nutrition. The method of this research is qualitative research, literature study and sub-data from articles and other references related to the research title. The results of the study are that parents play an important role in ensuring that their children grow and develop optimally, namely by optimizing nutrients applied in daily diet based on the child's age, developmental stages and activities. Optimal nutrition means a balance of carbohydrates, fats, proteins, vitamins and minerals, so that with this balance, children can grow healthy and achieve.